Halofuginone Sensitizes Lung Cancer Organoids to Cisplatin via Suppressing PI3K/AKT and MAPK Signaling Pathways - Li, Hefei; Zhang, Yushan; Lan, Xiaomei; Yu, Jianhua; Yang, Changshuang; Sun, Zhijian; Kang, Ping; Han, Yi; Yu, Daping (Frontiers in Cell and Developmental Biology, 2021)
Lung cancer is the leading cause of cancer death worldwide. Cisplatin is the major DNA-Damaging anticancer drug that cross-links the DNA in cancer cells, but many patients inevitably develop resistance with treatment. Identification of cisplatin sensitizer might postpone or even reverse the development of cisplatin-resistance. Halofuginone (HF), a natural small molecule isolated from Dichroa febrifuga, has been found to play an anti-tumor role. In this study, we found that HF inhibited the proliferation, induced G0/G1 phase arrest, and promoted apoptosis in lung cancer cells in a dose-dependent manner. To explore the underlying mechanism of this anti-tumor effect of halofuginone, we performed RNA-sequencing to profile transcriptome of NSCLC cells treated with or without halofuginone. Gene expression profiling and KEGG analysis indicated that PI3K/AKT and MAPK signaling pathways were top-ranked pathways affected by halofuginone. Moreover, combination of cisplatin and HF revealed that HF could sensitize the cisplatin-resistant patient-derived lung cancer organoids and lung cancer cells to cisplatin treatment. Taken together, this study identified HF as cisplatin sensitizer and dual pathway inhibitor, which might provide new strategy to improve prognosis of patients with cisplatin-resistant lung cancer.